Conduction mechanisms in metal/self‐assembled monolayer/metal junctions. (26th June 2019) - Etor, David; Dodd, Linzi E.; Balocco, Claudio; Wood, David
Abstract : The conduction mechanisms in metal–insulator–metal junctions where the insulator consists of a self‐assembled monolayer are investigated. Temperature dependence measurements from 2.5 to 300 K, show that the conduction is dominated by tunnelling only for temperatures below 20 K, while at higher temperatures surface‐limited and bulk‐limited mechanisms are observed. The experimental results are explained using a combination of direct (Simmons) tunnelling, Schottky emission, and Poole–Frenkel theory. Further insight is gained through numerical simulations based on the non‐equilibrium Green‐function formalism.